Pengaruh Kompensasi Manajemen dan Tingkat Utang Terhadap Manajemen Pajak Pada Perusahaan Industri Yang Terdaftar di BEI Tahun 2019 – 2023 - Setianingsih; Hardila, Ika; Norarita, Rika (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the effect of management compensation and debt levels on tax management in industrial companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The study uses a quantitative method with multiple regression analysis techniques through the Eviews 13 application. The sample used consisted of 13 companies that met the research criteria with a purposive sampling technique, namely the selection of samples based on certain criteria that are relevant to the research objectives. The results of the study indicate that management compensation has a negative and significant effect on tax management with a probability value of 0.0216 (<0.05). Conversely, the debt level has a positive and significant effect on tax management with a probability value of 0.0004 (<0.05). Simultaneously, the variables of management compensation and debt levels are able to explain 51.7% of the variation in tax management, as indicated by the adjusted R-squared value of 0.516880. The results of the F test also show that this research model is significant overall with a probability of 0.000001. These findings support agency theory which explains that managerial incentives and debt structure can influence tax management practices. This study provides implications that companies need to consider compensation policies and debt structures to optimize tax management efficiently and in accordance with regulations.